Communicating, Networking: Interacting The International Year of Global Understanding - IYGU - Robertson, Margaret E. (SpringerBriefs in Global Understanding,, 2016)
This book illustrates the benefits to be gained from digitally networked communication for health, education and transitioning economies in developing nations (Sierra Leone and Papua New Guinea) and developed nations. Growing powers of e-citizenship can help build sustainable futures. This small volume provides a collection of examples and ideas from which the authors hope will help build a wider resource. Understanding how to link everyday lives with global networks in the digital world in ways that add benefit for the world's people, and the health of the planet, is an ongoing project. IYGU recognises the integral roles of networking and communication systems, as well as interactions between people, near and far, as fundamental for building better futures. The global penetration of digital devices means everyday life, present and future, is inextricably linked with information technologies.